Employing remote sensing technique to monitor the influence of newly established universities in creating an urban development process on the respective cities - Cetin, Mehmet; Aksoy, Talha; Cabuk, Saye Nihan; Senyel Kurkcuoglu, Muzeyyen Anil; Cabuk, Alper (Elsevier BV, 2021)
Abstract Universities have a wide range of effects on the development of the cities, economic growth and socio-cultural structures of the communities. Accordingly, the Turkish government has encouraged the establishment of the higher education institutions to support the regional development especially in the underdeveloped areas. In this study, 13 universities established after 2006 in the eastern and south-eastern regions of the country were analysed for the determination of the effects of the university establishments in the land use patterns. To fulfil this aim NDVI differencing technique covering a period of 10–13 years was performed within the 1 km, 3 km and 5 km buffer rings around the campuses as well as the city centres. The city centres of three additional universities from the same region with older establishment periods varying between 1950 and 1980 were also analysed to compare the results. The results showed that the average of the negative changes in the city centre boundaries was 4.49%, and 6 of the 13 universities conduced to urban development, whereas the remaining 7 ones did not create a significant urban development.
Keywords: 9. Industry and infrastructure; 4. Education; 11. Sustainability; 8. Economic growth; 15. Life on land